2014
DOI: 10.7314/apjcp.2014.15.18.7583
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MicroRNA-21 Expression as a Potential Screening Biomarker for Colorectal Cancer: a Meta-analysis

Abstract: Background: Colorectal cancer (CRC) is a major cause of cancer-related death and cancer-related incidence worldwide. The potential of microRNA-21 (miR-21) as a biomarker for CRC detection has been studied in several studies. However, the results were inconsistent. Therefore, we conducted the present meta-analysis to systematically assess the diagnostic value of miR-21 for CRC. Materials and Methods: Using a random-effect model, the pooled sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Many previous studies screened for microRNA with significantly different expressions using a microRNA microarray in a small sample size and then validated the results by qRT‐PCR in a larger sample size. Thus, numerous systematic reviews and meta‐analyses have described the diagnostic efficiencies of microRNA . Most of these studies reviewed only 1 microRNA, while others reviewed all microRNA and conducted meta‐analyses including all of the diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies screened for microRNA with significantly different expressions using a microRNA microarray in a small sample size and then validated the results by qRT‐PCR in a larger sample size. Thus, numerous systematic reviews and meta‐analyses have described the diagnostic efficiencies of microRNA . Most of these studies reviewed only 1 microRNA, while others reviewed all microRNA and conducted meta‐analyses including all of the diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are a type of small-molecule endogenous RNAs, which play an important regulatory role in the growth process and the development of higher organisms (4). miR-21 is a member of the miRs and is highly expressed in various human tumors where it participates in cell proliferation, differentiation and apoptosis, and is closely related to the growth, invasion and metastasis of tumors (5). Chan et al found that suppression of miR-21 accelerated the apoptosis and increased the chemosensitivity of ovarian cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that miRNAs are important factors in the pathogenesis of human PTC (Jiang et al, 2014). Pallante et al have reported that miR-221, -222 and -181b were up-regulated in human PTCs (Pallante and Pich, 2000).…”
Section: Discussionmentioning
confidence: 99%